2015
DOI: 10.1161/strokeaha.115.009111
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Ischemic Stroke, and Coronary Heart Disease in Hypertensive Patients

Abstract: Stroke is the leading cause of permanent disability in China, 1 and ischemic stroke (IS) accounts for almost 80% of all strokes, 2 whereas coronary heart disease (CHD) is a major worldwide health threat. In tandem with the economic success of China, the number of individuals in China with IS and CHD has increased significantly in recent years, with stroke resulting in 301 million disability-adjusted life-years. 3CHD in Chinese adults aged 35 to 84 years is predicted to increase by 64% during the period 2020-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 48 publications
5
58
1
6
Order By: Relevance
“…In China, the prevalence of hyperuricemia is w13% (31), and the prevalence of tHcy concentrations $15 mmol/L is 27-30% (32,33), without the mandatory folic acid fortification of foods. In China, the estimated number of adults with hyperuricemia is 170 million, and the number of adults with tHcy concentrations $15 mmol/L is 350 million.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence of hyperuricemia is w13% (31), and the prevalence of tHcy concentrations $15 mmol/L is 27-30% (32,33), without the mandatory folic acid fortification of foods. In China, the estimated number of adults with hyperuricemia is 170 million, and the number of adults with tHcy concentrations $15 mmol/L is 350 million.…”
Section: Discussionmentioning
confidence: 99%
“…The A1298C variant results in substitution of glutamate (Glu) to alanine (Ala) at codon 429 in the S-adenosylmethionine regulatory domain of the MTHFR protein [18, 19]. The MTHFR C677T genetic variant can lead to elevated levels of plasma tHcy and, thus, increased ischemic stroke risk [20, 21], data of which have been further confirmed in other studies [12, 13, 22]. tHcy is thought to increase thrombotic risk through induction of endothelial injury in the venous and arterial vasculature [23].…”
Section: Introductionmentioning
confidence: 93%
“…For example, upregulated tHcy can induce cell apoptosis by increased ROS levels through activation of the p38 MAPK pathway [11]. In the context of stroke, the elevated levels of plasma tHcy were shown to associate with increased risk of ischemic stroke [12, 13]. MTHFR is localized at chromosome 1 p36.3 in the human genome, and to date there are over 40 point mutations or SNPs in the MTHFR gene identified [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have shown that a raised blood Hcy level -hyperhomocysteinemia (HHC) is a risk factor for cardiovascular events, including ischemic heart disease, chronic kidney disease and cerebrovascular disease [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Acta Veterinaria-Beograd 2017, 67 (2), [254][255][256][257][258][259][260][261][262][263][264][265][266][267][268][269][270] MNOGOBROJNI MEHANIZMI UKLJUČENI SU U STIMULATORNE EFEKTE HOMOCISTEINA NA GLATKU MUSKULATURU DUODENUMA PACOVA STOJANOVIĆ Marija, ŠĆEPANOVIĆ Ljiljana, MITROVIĆ Dušan, ŠĆEPANOVIĆ Vuk, ŠĆEPANOVIĆ Radomir, DJURIC Marko, ILIĆ Slobodan, ŠĆEPANOVIĆ Teja, DJURIC Dragan Novije studije potvrdile su povezanost hiperhomocisteinemije i gastrointestinalnih oboljenja, mada su i dalje nepoznati direktni efekti homocisteina na gastrointestinalnu reaktivnost. Cilj ovog rada bio je da demonstrira kako homocistein moduliše azot monoksid zavisnu duodenalnu relaksaciju i da li holinergički receptori i K+ kanali imaju uticaja na stimulaciju motiliteta, kao i da ispita da li je oksidativni stres udružen sa efektima homocisteina.…”
unclassified